Greater complexity and monitoring of the new Kidney Allocation System: Implications and unintended consequences of concentric circle kidney allocation on network complexity. Issue 6 (2nd January 2021) - Adler, Joel T.; Husain, Syed A.; King, Kristen L.; Mohan, Sumit
Abstract: The deceased donor kidney allocation system in the United States has undergone several rounds of iterative changes, but these changes were not explicitly designed to address the geographic variation in access to transplantation. The new allocation system, expected to start in December 2020, changes the definition of "local allocation" from the Donation Service Area to 250 nautical mile circles originating from the donor hospital. While other solid organs have adopted a similar approach, the larger number of both kidney transplant centers and transplant candidates is likely to have different consequences. Here, we discuss the incredible increase in complexity in allocation, discuss some of the likely intended and unintended consequences, and propose metrics to monitor the new system. Abstract : With implementation of the new US kidney allocation system, the authors discuss the incredible increase in allocation complexity, likely consequences, both intended and unintended, and possible metrics to best monitor impact. See Formica's editorial on page 1996 .